Striving for Islamic governance - Abdul Rashid Moten (International Institute of Islamic Thought, 2015)
Muslim-majority countries are striving with some success to reshape their governance models along Islamic lines. Some countries have opted for implementing the Shari‘ah, whereas others have focused on applying personal status laws. This study analyzes the attempts made by specific leaders in the Islamic Republic of Pakistan, the secular Republic of Turkey, and multi-ethnic Malaysia to improve their governance models in the areas of human, economic, and social development. As these countries adopted different strategies, the resultant models of Islamic governance are due largely to the contexts and features of their respective societies. Unlike Pakistan’s authoritarian top-down approach, Turkey and Malaysia largely embraced democratic principles, operated a new hybrid economic model that combined the characteristics of Islamic and capitalist market systems, and worked closely with the West. Many consider these two models, although “partial” in their approach, to be examples of open and democratic Islamic governance that are relatively appreciated by the West. Keywords